The green teen : the eco-friendly teen's guide to saving the planet - Savedge, Jenn, 1972- (Gabriola Island, BC : New Society Publishers, 2009)
Presents advice and tips on how to live an environmentally-conscious life, making decisions on purchases, food consumption, waste management, and social activism with the environment in mind.